Knowledge Relations Regarding Health Protocols with the Behavior of Pregnant Women to Prevent Covid-19 Transmission in the Lambunu 2 Health Center UPTD Work Area - Lisnawati (Universitas Muhammadiyah Palu, 2023)
Background: The target number of pregnant women is 525 people, and the number of deaths of pregnant women with Covid-19 at the Lambunu 2 Health Center in 2021 is one person. Therefore researchers need to research the relationship between knowledge of health protocols and the behavior of pregnant women to prevent the transmission of Covid-19. Objective: This study aims to determine the relationship between knowledge about health protocols and the behavior of pregnant women to prevent the transmission of Covid-19 in the Lambunu 2 Health Center UPTD Working Area. Method: The design of the study is an analytic survey with a cross-sectional approach. The research in the Lambunu 2 Health Center work area was conducted from March 15 to May 30 2022. The population in this study were all pregnant women in the Lambunu 2 Health Center area. The sample in this study is pregnant women who came to the Lambunu 2 Health Center, a total of 39 respondents. The instrument used is a questionnaire. The data analysis used is the Chi-Square test. Result: The results show a correlation between respondents' knowledge about health protocols and behavior to prevent the transmission of Covid-19. Twenty-three people (92%) show good behavior and good knowledge as a result. Three people (50%) show a lack of behavior and knowledge. Obtained p value = 0.000 ≤ α = 0.05. Conclusion: This study concludes that there is a relationship between knowledge about health protocols and the behavior of pregnant women to prevent transmission of Covid-19 in the UPTD Work Area of the Lambunu 2 Health Center. The results of this study provide an understanding to pregnant women about health protocols to prevent the transmission of Covid-19.